Analisis Potensi Keruntuhan Bendungan Bringe Akibat Overtopping dan Pemetaan Area Terdampak dengan Menggunakan HEC-RAS 6.6.0 - Fahrezi, Muhamad Azmi; Wicaksono, Muhammad Hasan; Hariati, Feril (Jurnal Komposit: Jurnal Ilmu-ilmu Teknik Sipil, 2026)
Dams are vital infrastructure that play an important role in irrigation water supply, flood control, and water resource conservation. However, dam failure can lead to catastrophic flooding that threatens human lives and causes significant material losses. This study aims to analyze the potential failure of Bringe Dam due to the overtopping mechanism and to identify the characteristics and distribution of flood inundation in downstream areas using the HEC-RAS 6.6.0 software. The simulation results show that the dam failure due to overtopping produced a peak outflow discharge of 103.69 m³/s with a breach formation time of approximately 1.24 hours. The maximum inundation area reached 77.49 hectares, affecting several villages downstream, with a maximum water depth of 8.11 m and an average depth of 2.07 m in the affected areas. Based on these results, it can be concluded that Bringe Dam poses a high hazard potential in the event of a failure caused by overtopping. Therefore, mitigation measures such as increasing spillway capacity, monitoring water surface elevation regularly, and developing an emergency response plan and evacuation routes for downstream communities are highly recommended.